QORAQALPOG‘ISTONDA JAMOALASHTIRISH VA UNING OQIBATLARI - Abdukarimov, A.A. (SCIENCE and SOCIETY, 2025)
The article discusses the processes of collectivization of agriculture in Karakalpakstan and its consequences.